Obesity and leptin in breast cancer angiogenesis - Lagarde, Courtney B.; Thapa, Kapil; Cullen, Nicole M.; Hawes, Mackenzie L.; Salim, Khudeja; Benz, Megan C.; Dietrich, Sophie R.; Burow, Brandon E.; Bunnell, Bruce A.; Martin, Elizabeth C.; Collins-Burow, Bridgette M.; Lynch, Ronald M.; et al. (Frontiers in Endocrinology, 2024)
At the time of breast cancer diagnosis, most patients meet the diagnostic criteria to be classified as obese or overweight. This can significantly impact patient outcome: breast cancer patients with obesity (body mass index > 30) have a poorer prognosis compared to patients with a lean BMI [1-3]. Obesity is associated with hyperleptinemia, and leptin is a well-established driver of metastasis in breast cancer [4,5]. However, the effect of hyperleptinemia on angiogenesis in breast cancer is less well-known. Angiogenesis is an important process in breast cancer because it is essential for tumor growth beyond 1mm 3 in size as well as cancer cell circulation and metastasis [6]. This review investigates the role of leptin in regulating angiogenesis, specifically within the context of breast cancer and the associated tumor microenvironment in obese patients.